1957
DOI: 10.1111/j.1423-0410.1957.tb03430.x
|View full text |Cite
|
Sign up to set email alerts
|

A Gene, y, Modifying the Blood Group Antigen A

Abstract: Summary Evidence is given for the existence in man of a locus Yy.The very rare genotype yymodifies the development of the A antigen in the red cells and, to a very much less extent, in the saliva; the B and H antigens are not affected. The Yylocus is not closely linked to the ABOlocus. Résumé Les études sérologiques et génétiques présentées dans ce travail font penser qu'il existe chez l'homme une paire de gènes Yy; le rare genotype yyinfluencerait la puissance du facteur A dans les érythrocytes, beaucoup moin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
24
0

Year Published

1961
1961
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(27 citation statements)
references
References 5 publications
3
24
0
Order By: Relevance
“…It may be discussed whether the B variant of IM is due to a genetic mechanism analogous to the suppressor genes 'yy' described by Weiner et al [11] as operating in Am persons. However, Ayy persons secrete normal amounts of A substance in their saliva, whereas the B substances in IM saliva was markedly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…It may be discussed whether the B variant of IM is due to a genetic mechanism analogous to the suppressor genes 'yy' described by Weiner et al [11] as operating in Am persons. However, Ayy persons secrete normal amounts of A substance in their saliva, whereas the B substances in IM saliva was markedly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The position is extremely complex and results of studies suggest that gene modifications may occur at least four loci, X, A, Y and H, all of which may give rise to variant bloods [7,9,10,13,14,19]. …”
Section: Discussionmentioning
confidence: 99%
“…Har., was an example of A gene suppression as her genotype was found to be AxO. Studies on her saliva revealed the presence of A and H substances and her cells were found to be strongly H positive, so it was apparent that this was a further example of the Am phenotype [3,9,11,19,20,28,31,32], …”
mentioning
confidence: 99%